STRATEGY FOR THE DEVELOPMENT OF THE LAPONU-PONU LAKE TOURISM OBJECT, RONOKOMEA VILLAGE, POLEANG BARAT DISTRICT, BOMBANA REGECY, INDONESIA - Novrian, Ardina (Geographica: Science and Education Journal, 2023)
Laponu-ponu Lake Tourism is a natural tourism object located in Ranokomea Village, Poleang Barat District, Bombana Regency which has attractive natural and artificial attractions. Laponu-Ponu lake tourism object is seen from its accessibility, facilities and infrastructure that have not been developed properly so that the number of visitors has decreased. The problem studied in this study is how to develop a tourism object in Laponu-Ponu lake. The purpose of this research is to know the strategy of developing Laponu-ponu lake tourism object. This study used descriptive qualitative method. The analysis used in this study is a SWOT analysis (strengths, weaknesses, opportunities, arts). The results of this study indicate that attractions that can be developed include natural tourist attractions, artificial tourist attractions and strategic development objects for Laponu-ponu lake tourism. The strategies for developing Laponu-Ponu lake tourism objects include utilizing natural resources as tourist destinations so as to increase local revenue, making unique and modern tourism, strategies for improving and maintaining existing facilities, facilities and infrastructure, increasing tourist attractions and increasing accessibility by maintain the condition of roads which are currently under construction, promote the Laponu-ponu lake tourism object with existing technology (social media), and provide a garbage disposal area around the tourism object.